ASSESSMENT OF BUSINESS EFFICIENCY OF SME IN AGRIBUSINESS IN MUNICIPALITIES OF THE SERBIAN DANUBE BASIN - Maletić, Radojka; Popović, Blaženka (Economics of Agriculture, 2011)
Based on seven economic indicators, which each in their own way measure the level of development, the I-square distance was applied and rank of municipalities located in the Danube basin defned according to presence of small and medium enterprises in agribusiness. Subsequently, by DEA methodology, as and exceptional technique to determine the effectiveness of several entities in the same feld, it was analyzed how changes in the inputs and outputs affect the end result. Study can be used as guideline for more intensive and even intra-regional development within the territory of Danube basin, and prevent the migration of young people from villages and open possibilities for their employment in small and medium entrepreneurship.